Identification of highly potent competence stimulating peptide-based quorum sensing activators in Streptococcus mutans through the utilization of N-methyl and reverse alanine scanning. Issue 6 (15th March 2019) - Bikash, Chowdhury Raihan; Tal-Gan, Yftah
Graphical abstract: Abstract: Quorum sensing (QS) controls the pathogenic behavior of Streptococcus mutans, a primary cause of dental caries. S. mutans uses the competence stimulating peptide (CSP) to control mutacin production, a bacteriocin utilized by S. mutans to outcompete different commensal bacteria in mixed biofilm environments. In this study, we performed an N -methyl scan of an 18-CSP-based scaffold lacking the first two amino acid residues that were shown to be dispensable, to gain important mechanistic insight as to the role of backbone amide protons in the interaction between CSP and the ComD receptor. We then utilized the reverse alanine approach to develop CSP-based analogs with enhanced activities. The two most potent analogs were found to induce bacteriocin production at sub-nanomolar concentration using an interspecies inhibition assay. Overall, our analysis revealed that the 18-CSP sequence is not optimized and can be improved by replacement of multiple positions with alanine. Our results further suggest that the hydrophobic residues in S. mutans 18-CSP are involved in both receptor binding and activation.